Nascent and Complex: What Is the Focus of Trust Research?Nascent and Complex: What Is the Focus of Trust Research? by KeytonJoann, North Carolina State University, Raleigh, and faye 1. smith, Missouri Western State University, St. Joseph - Keyton, Joann (Academy of Management Review, 2008)
The article reviews the book "Nascent and Complex: What Is the Focus of Trust Research?" by Joann Keyton.